Binocular Input Coincidence Mediates Critical Period Plasticity in the Mouse Primary Visual Cortex - Chen, Xiao-jing (J Neurosci, 2014)
Classical studies on the development of ocular dominance (OD) organization in primary visual cortex (V1) have revealed a postnatal critical period (CP), during which visual inputs between the two eyes are most effective in shaping cortical circuits through synaptic competition. A brief closure of one eye during CP caused a pronounced shift of response preference of V1 neurons toward the open eye, a form of CP plasticity in the developing V1. However, it remains unclear what particular property of binocular inputs during CP is responsible for mediating this experience-dependent OD plasticity. Using whole-cell recording in mouse V1, we found that visually driven synaptic inputs from the two eyes to binocular cells in layers 2/3 and 4 became highly coincident during CP. Enhancing cortical GABAergic transmission activity by brain infusion with diazepam not only caused a precocious onset of the high coincidence of binocular inputs and OD plasticity in pre-CP mice, but rescued both of them in dark-reared mice, suggesting a tight link between coincident binocular inputs and CP plasticity. In Thy1-ChR2 mice, chronic disruption of this binocular input coincidence during CP by asynchronous optogenetic activation of retinal ganglion cells abolished the OD plasticity. Computational simulation using a feed-forward network model further suggests that the coincident inputs could mediate this CP plasticity through a homeostatic synaptic learning mechanism with synaptic competition. These results suggest that the high-level correlation of binocular inputs is a hallmark of the CP of developing V1 and serves as neural substrate for the induction of OD plasticity.